Science Teachers' Representations of Classroom Practice in the Process of Formative Assessment Design. Issue 7 (23rd November 2016) - Heredia, Sara C.; Furtak, Erin Marie; Morrison, Deb; Renga, Ian Parker
Abstract: Formative assessment has been recognized as an essential element of effective classroom practice; as a result, teachers are increasingly required to create formative assessments for their classrooms. This study examines data drawn from a long-term, site-based professional development program that supported a department of biology teachers in the iterative design and enactment of common formative assessment tools. We analyze teacher conversations to understand how teachers collaborated to design formative assessments. Results indicate that when teachers attended to problems of practice related to teaching evolution, increased transparency in their talk helped build consensus about the design of formative assessment tools. These results highlight the importance of encouraging transparency in teacher dialog when they are engaged in collaborative design of formative assessments.